Neuroscience and Translation - Cuiling Zhang (Translation and Interpreting : the International Journal of Translation and Interpreting Research, 2023)
In the past decades, researchers have established various theories and approaches to explore the nature of translation, this “most complex type of event yet produced in the evolution of the cosmos” (Richard, 1953:250). Especially since the inception of Translation Studies as an academic discipline in the 1970s, translation scholars have drawn extensively on tools, concepts, and theories from other disciplines, such as sociology, anthropology, psychology, and biology in their efforts to explore the many facets of translation and interpreting. Now, neuroscience came to the fore. As the study of the nervous system, the task of neuroscience is to understand brain processes— how we perceive, act, learn, and remember – and explain behavior in terms of brain activities (Kandel et al., 2012, pp. 3-5). For decades, neuroscientists have explored human language and have produced remarkable studies on language development and learning. Yet the findings on how the brain handles language processing are still primarily based on monolinguals. The mental process of multilingual people and many other aspects of the transfer between different languages remain largely unsettled. This inspired Maria Tymoczko to explore the neurological mechanisms involved in translating, a field that she dubs as one of the “known unknowns” in translation studies (Tymoczko, 2012) and believes will fundamentally influence the way translation is thought about and ultimately illuminate many aspects of translation, including the “black box” of the individual translator.